IoT Based Smart Classroom - Prajas Kadepurkar; Prim Rochelle Dsouza; Nivya Jomichan (Universitas Sanata Dharma, 2021)
A classroom is a place where there is always room for development; therefore just as the development for a student results in the ease of living, similarly a smart classroom focuses on the structural development leading to effective time and energy utilization. This project offers three major upgradation in classroom; the first being able to book a classroom dynamically using Raspberry Pi and toggling lights and fans using NodeMCU and a mobile application which also helps notify a student about the subject of the lecture, the time and the venue related to the commencement of a period. The second section of this project inputs the attendance of a student check in, using a portable real-time biometric system whose data can further be used to calculate the attendance statistics of each student which can be viewed by the respective student or the teachers can keep a track on their own assigned class using the mobile application. And the last part of the project focuses on keeping track of all the lights and fans, which are on after the lecture. After the lecture is done, it will check the status of the room, whether some other teacher for some other subject is using the lecture hall. Also when the teacher ends the class, the lights and fans will be switched off after 5 minutes buffer provided for the students to checkout. It will wait for 15 minutes and if it still does not receive any request then it will switch off the lights and fans of that particular lecture hall.